2012
DOI: 10.1590/s0104-66322012000200013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lyophilized liposomes produced with non-purified soy lecithin: a case study of casein hydrolysate microencapsulation

Abstract: -A commercial casein hydrolysate was microencapsulated in liposomes produced with non-purified soy lecithin, cryoprotected with two different disaccharides and lyophilized. The encapsulation efficiency of casein hydrolysate ranged from 30 to 40%. The powders were analyzed by differential scanning calorimetry (DSC), scanning electron micrography (SEM), infrared spectroscopy (FTIR) and wide angle X-ray diffraction (WAXD). DSC data revealed the presence of an exothermal transition in empty lyophilized liposomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 41 publications
1
49
1
1
Order By: Relevance
“…Notably, our findings represent the highest EE reported for food-derived peptides in liposome carriers. This is contrary to the lower EE of 40-60% reported for casein peptides in liposomes (Yokota, Moraes, & Pinho, 2012;Morais, Da Silva Barbosa, Delvivo, Mansur, Cristina De Oliveira, & Silvestre, 2004), which was attributed to limited peptide-carrier interaction due to the repulsion of the negatively charged casein phosphopeptides and the anionic head groups of the phospholipids in the liposomes (Mohan et al, 2015b). Similarly, lower EE has been reported for negatively charged bovine serum albumin (Liu, Ye, Liu, Liu, Han, & Singh, 2015), but encapsulation of marine protein-derived peptides in liposomes has resulted in a relatively higher EE of up to 80% (da Rosa Zavereze et al, 2014, Mosquera et al, 2014.…”
Section: Effect Of Whey Peptide Molecular Weight On Encapsulation Effcontrasting
confidence: 91%
See 1 more Smart Citation
“…Notably, our findings represent the highest EE reported for food-derived peptides in liposome carriers. This is contrary to the lower EE of 40-60% reported for casein peptides in liposomes (Yokota, Moraes, & Pinho, 2012;Morais, Da Silva Barbosa, Delvivo, Mansur, Cristina De Oliveira, & Silvestre, 2004), which was attributed to limited peptide-carrier interaction due to the repulsion of the negatively charged casein phosphopeptides and the anionic head groups of the phospholipids in the liposomes (Mohan et al, 2015b). Similarly, lower EE has been reported for negatively charged bovine serum albumin (Liu, Ye, Liu, Liu, Han, & Singh, 2015), but encapsulation of marine protein-derived peptides in liposomes has resulted in a relatively higher EE of up to 80% (da Rosa Zavereze et al, 2014, Mosquera et al, 2014.…”
Section: Effect Of Whey Peptide Molecular Weight On Encapsulation Effcontrasting
confidence: 91%
“…The diameters of the liposomes produced in this study fall within the range previously reported for food peptide-loaded liposomes (Morais et al, 2004;Mosquera et al, 2014Mosquera et al, , 2016Yokota et al, 2012). Interestingly, the mean diameters of the peptide-loaded liposomes were larger than those of the empty liposomes by about 30 to 90 nm (Table 1).…”
Section: Mean Particle Sizesupporting
confidence: 87%
“…They have a unique ability of encapsulating hydrophobic, hydrophilic and amphiphilic compounds [16,17]. Drugs with varying hydrophobicities can be encapsulated in the phospholipid bilayer, in the entrapped aqueous core, or at the bilayer interface [18].…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes, or phospholipid vesicles, are versatile carriers for both hydrophilic and hydrophobic bioactive molecules, with advantages including being natural, biodegradable and non-toxic (Kosajaru et al, 2006). Food applications of these colloidal structures greatly increased in the last decade, and many examples of encapsulated substances in food formulations can be found in the literature, such as ferrous sulphate (Xia & Xu, 2005;Kosajaru et al, 2006), enzymes (Benech et al, 2003;Xia et al, 2006;Nongonierma et al, 2009), antimicrobial agents (Were et al, 2003(Were et al, , 2004Teixeira et al, 2008;Malheiros et al, 2010), ferrous glycinate (Ding et al, 2009(Ding et al, , 2011, vitamins (Maranasco et al, 2011), functional peptides (Morais et al, 2003;Hwang et al, 2010;Yokota et al, 2012), salidroside (Fan et al, 2007), essential oils (Gortzi et al, 2007(Gortzi et al, , 2008van Vuuren et al, 2010;Yoshida et al, 2010) and carotenoids (Xia et al, 2011). An important issue with the production of these dispersions, however, is the scale-up.…”
Section: Introductionmentioning
confidence: 99%